DEVELOPMENT STRATEGY FOR SUNFLOWER OIL ENTERPRISES IN UKRAINE - Virkovska, Anastasiya; Lotysh, Oksana; Liakhovych, Larysa; Kostetska, Nataliia (Socio-economic relations in the digital society, 2025)
The relevance of the research topic is driven by the need to develop an effective strategy for ensuring the long-term growth of sunflower oil enterprises in Ukraine. The paper analyzes the current state of sunflower oil production. It establishes that, despite wartime challenges, Ukraine remains one of the world leaders in producing and exporting sunflower oil. Sunflower oil enterprises’ macro-, meso-, and internal environments are analyzed and evaluated using expert methods. To assess the macro-environment of domestic enterprises, their components are identified, analyzed, and evaluated, considering their indirect yet significant influence on business performance. It is settled that the political, economic, and technological components exert the greatest influence on sunflower oil enterprises, and the overall evaluation indicates a satisfactory state of the macroenvironment. In studying the meso-environment, key elements are identified that should be considered when formulating development strategies. Competitors and consumers are the most influential components, and the integral assessment of the meso-environment indicates favourable conditions for the development of sunflower oil enterprises. The internal environment analysis is conducted using the case of a private company (PC) “Oliyar”, one of Ukraine’s largest sunflower oil producers. The SWOT analysis method is used to determine internal strengths, external opportunities, and threats. Based on the research findings, a matrix for selecting development strategies for sunflower oil enterprises is constructed, encompassing three types: growth strategies, market position retention strategies, and retrenchment strategies. It is determined that PC “Oliyar” is currently employing a market position retention strategy to maintain its market share, increase sales volumes, and boost profits. Considering possible future events and emerging external trends, there is a likelihood of a shift in the enterprise’s strategic direction. It is emphasized that sunflower oil enterprises must continuously monitor the external environment, systematically analyze business processes, assess performance indicators, and, when necessary, develop new strategies.